Perilaku Agresif Pada Suporter Sepakbola - Alghaffar, Rachmatullah Lutfi; , Dr. Wiwien Dinar Pratisti,M.Si (2017)
Aggressive behavior is a behavior that aims to hurt and harm other. Aaggressive behavior can cause harm to other the people or themselves. One of the factors that influenced the aggressive behavior football's supporters. Supporters are one form of social group which relatively disorganized and happened to see something. Thesse kind of crowds are almost same as the ordinary audience but not planned well. The purpose of research is to describe the aggressive behavior on the football's supporters. This study uses qualitive methods. Informant from the research were selescted by purposive sampling with characteristic of the supporters of football who lived in Surakarta. The results of the study indicate that 1)aggressive behavior arises supporter for thier rivalry football club during a match between supporters and their provocation 2)supporter verbally aggressive behavior that is song by obscenities and racist, then physically throw objects around the existing and damaging facilities 3)aggressive behavior found on football's supporters who were singing searwords songs, then physically thowing. Aggressive behavior of supporters arises because of the rivalry between supporters and mutual provocation, then raised verbally aggressive behavior and physical